Detection of carcinoembryonic antigens using a wavy gold–silver alloy nanoplate enhanced surface plasmon resonance imaging biosensor. Issue 45 (7th November 2022) - Wu, Jiangling; Zhang, Qiongyuan; Kang, Lina; Wu, Xiaotian; Li, Daikun; Wang, Yi; Huang, Yu; Xue, Jianjiang
Abstract : Wavy gold–silver alloy nanoplates are signal enhancers in this surface plasmon resonance imaging measurement for the detection of CEA. Abstract : Carcinoembryonic antigen (CEA) is regarded as a promising broad spectrum tumor biomarker for clinical diagnosis, progression, and prognosis. Surface plasmon resonance imaging (SPRi) was considered as one of the powerful tools for immunoassay with advantages of label-free, real-time detection with high-throughput. Herein, wavy gold–silver alloy nanoplates functionalized with anti-CEA antibodies providing high protein loading capacity and high mass are used as signal enhancers for CEA detection through SPRi sandwich assay. The present method exhibits a dynamic range for CEA determination from 0.1 to 312.5 ng mL −1 and a detection limit of 0.55 ng mL −1, well below normal physiological levels. This biosensing approach demonstrates the advantages of wavy gold–silver alloy nanoplates compared to conventional gold nanoparticles as a signal amplifier to enhance the SPRi signal, which is expected to become a new prospect for detection of cancer markers in biomedical research and clinical diagnosis.